Standardization of a Preclinical Colon Cancer Model in Male and Female BALB/c Mice: Macroscopic and Microscopic Characterization from Pre-Neoplastic to Tumoral Lesions - Elizabeth Correa; Juan Pablo Rendón; Vanesa Bedoya-Betancur; Juliana Montoya; Julian Muñoz Duque; Tonny W. Naranjo (Biomedicines)
Background/Objetives: This study standardized a chemically induced colorectal cancer (CRC) model using azoxymethane (AOM) and dextran sodium sulfate (DSS) in BALB/c mice, replicating the progression from preneoplastic lesions to adenocarcinoma observed in human colorectal carcinogenesis. Methods: The CCR-AOM/DSS model was standardized in male and female BALB/c mice. Two protocols were tested. Subsequently, the positive control group was established with nine evaluation points. Tumor progression was characterized histopathologically and corroborated by methylene blue staining and scanning electron microscopy. Results: Two cycles of 2% DSS combined with a single injection of AOM (10 mg/kg) were necessary to induce adenocarcinoma in 100% of the mice, with no significant sex-based differences in tumor development. Females showed earlier tumor susceptibility under certain protocols. Inflammatory processes played a critical role in tumorigenesis, with neutrophil infiltration and fibrosis observed. Conclusions: The findings align with previous reports, emphasizing the influence of DSS cycles, molecular weight, and mouse strain on model outcomes. This standardized model provides a reliable platform for the preclinical evaluation of novel preventive and therapeutic strategies for CRC.